Building Excellence: Strategic Management in Thai Private Schools Amidst Global Educational Shifts - โฆษิตพิมานเวช เอกราช (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper explores the strategic management practices necessary for Thai private schools to maintain educational excellence amidst global educational shifts. As private schools in Thailand navigate the challenges of integrating technology, fostering 21st-century skills, and promoting sustainability, strategic leadership becomes crucial. The paper highlights the importance of balancing innovation with the preservation of Thai cultural values, managing financial constraints, and enhancing teacher development. Through collaboration with local communities and global educational institutions, Thai private schools can position themselves as leaders in the global educational landscape while staying true to their core identity. The paper concludes with recommendations for continuous evaluation and adaptation to ensure long-term success.